Fatal Outcome of European Tick-borne Encephalitis after Vaccine Failure - Sendi, Parham; Hirzel, Cédric; Pfister, Stefan; Ackermann-Gäumann, Rahel; Grandgirard, Denis; Hewer, Ekkehard; Nirkko, Arto C. (Frontiers in Neurology, 2017)
Tick-borne encephalitis is a viral disease affecting the central nervous system. It is endemic in Switzerland with 200–250 notified cases annually. Active immunization is effective for persons in all age groups. Vaccine failure is rare, in particular after a completed vaccination course. Here, we describe the case of 67-year-old man with a fatal outcome despite vaccination. The diagnosis was confirmed by extensive postmortem analyses. The diagnostic challenges of vaccine failure in tick-borne encephalitis and the dynamics of the immune response in vaccination breakthrough are discussed.